2021
DOI: 10.1108/tr-09-2020-0458
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing Chinese residents' post-pandemic outbound travel intentions: an extended theory of planned behavior model based on the perception of COVID-19

Abstract: Purpose This study aims to explore the factors influencing the post-pandemic intentions of Chinese residents to participate in outbound travel. The mechanism by which residents' perception of the coronavirus disease (COVID-19) influenced their outbound travel intentions are studied. Design/methodology/approach This study developed an extended theory of planned behavior (TPB) model and used structural equations to analyze data received from 432 questionnaires. Responses were obtained through a combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
120
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(146 citation statements)
references
References 49 publications
20
120
3
3
Order By: Relevance
“…In a similar vein, Perić et al (2021) observed that the risk perceptions of Serbian tourists negatively affected their intentions to travel during the pandemic while Garcia and Leoni (2021) revealed that individuals exposed to COVID-19 had a relatively higher willingness to travel. Contributing to the growing literature in the area, Liu et al (2021) found that the perception of COVID-19 had a negative impact on outbound travel by individuals residing in China while risk tolerance had a negative moderating influence on the association between COVID-19 perception and travel intentions after the pandemic. In addition, Xie et al (2021) revealed a significant moderating impact for empathy and perceived waiting time on the association between risk message frames and post-pandemic travel intentions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar vein, Perić et al (2021) observed that the risk perceptions of Serbian tourists negatively affected their intentions to travel during the pandemic while Garcia and Leoni (2021) revealed that individuals exposed to COVID-19 had a relatively higher willingness to travel. Contributing to the growing literature in the area, Liu et al (2021) found that the perception of COVID-19 had a negative impact on outbound travel by individuals residing in China while risk tolerance had a negative moderating influence on the association between COVID-19 perception and travel intentions after the pandemic. In addition, Xie et al (2021) revealed a significant moderating impact for empathy and perceived waiting time on the association between risk message frames and post-pandemic travel intentions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Focussing on the future of travel, Sanjita et al (2021) predicted the number of foreign tourists using an ANN approach. Numerous studies have been conducted to explain the impact of COVID-19 on individuals’ intentions to travel (Zheng et al, 2021; Pappas, 2021 , Liu et al, 2021 , Gupta et al, 2021 ). For instance, in a study on adult residents of Greece, Pappas (2021) confirmed the impact of the pandemic on holiday intentions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In addition, the fact that health and travel restrictions were relaxed meant that individuals could feel that they had more control over their decisions and behaviors than in the earlier stages of the pandemic. Consequently, once barely leaving their homes, pandemic-fatigued people might come to have great enthusiasm about travel again due to the lessened restrictions and increased perceived behavioral control [58]. Based on these arguments, the first hypothesis of the study was created.…”
Section: Pandemic Fatigue and Revenge Travelmentioning
confidence: 99%
“…Positive attitudes tend to positively influence behavioral intentions. Although TPB initially appeared in the organizational behavior literature, in recent years, TPB has been used in various studies on consumer behavior (Kement et al, 2020;Sumaedi et al, 2020;Kapoor & Singhal, 2021;Liu et al, 2021). Including the behavior of buying masks (Shah et al, 2020).…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%